Healthy snack food campaign through educational games for elementary school student - Rizki Andriani; Fitri Apriani; Siti Damayanti; Orita Satria; Yulfa Aulia; Agus Irmansyah; Nurromsyah Nasution (University of Merdeka Malang, 2023)
Elementary school students like various snacks in the school environment, which frees children to choose the food and drinks available. They tend to consume foods containing causative spices, sweet foods, and beverages, and foods with additional ingredients, which will cause things that are not good for children's health. There are still many students who need help understanding about healthy snacks food. Education on healthy snacks in schools is not optimal because knowledge related to these snacks food still needs to be better socialized. This community service activity aims to increase knowledge about healthy snacks in elementary school students through educational games. The methods are socialization, focus group discussion, game simulation through snake and ladder educational games, healthy snack food puzzles, self-evaluation, and documentation. The results obtained from this activity were in the form of increasing the knowledge score of healthy snack food after education and educational games and commitment from partners to incorporate healthy snack food materials into PJOK subjects. This result shows that knowledge of healthy snacks can be improved through snake and ladder educational game activities and beneficial snack food puzzle games. It is recommended that the school continuously allocate time regularly for healthy snack food education for all students.